TA010 and TA011 antibodies label mouse glucagon-secreting alpha cells by immunohistochemistry - Ruetsche, Audrey; leyss, Simon; Liborova, Karolina; Maître, Marie; Manghetti, Livia; Mencier, Lucie; Moudarres, Lana; Najand, Gaelle; Roch, Laura; Durual, Stéphane; Jauslin, Tania; Guilhen, Cyril; et al. (Antibody Reports, 2023)
The recombinant antibodies TA010 and TA011 detect by immunohistochemistry the glucagon-secreting alpha cells in mouse pancreatic islets.